Awareness and attitudes of academics in Türkiye toward the impacts of global climate change - Ökde, Fatma (Environmental Research and Technology, 2025)
This study aims to reveal the awareness and attitudes of academics in Türkiye on the impacts of global climate change. It utilized quantitative research methodology. The data was collected through a survey sent to the e-mail addresses of academics between December 2023 and May 2024. The sample comprises 421 respondents (212 male and 209 female; the duration of their academic career ranges from 1 to 16 years) affiliated with nearly 100 universities. They were selected through the convenience sampling method. The data was collected from the survey and analyzed using the SPSS 27 software including frequency distributions, mean calculation, exploratory factor analysis, and reliability analysis. The reliability levels of the sub-dimensions were tested with the Alpha method. The findings indicate that the global climate change awareness scale consists of four sub-dimensions: awareness of global organizations and agreements, impacts on the natural and human environment, energy consumption relations, and causes of emergence. 62.430% of the total variance is explained by these four sub-dimensions. All sub-dimensions are reliable (α ≥ .70) (Kaiser-Meyer-Olkin Sampling Adequacy: 0.870; Bartlett’s Test of Sphericity P Value: .000; Total Variance Explained: 62.430). Findings also show that the sample had medium to high awareness of global climate change and its effects. This study concludes that academics advocated the need to raise awareness of society as the most effective method to combat global climate change and the need to take international collaboration and legal measures.